2013
DOI: 10.4103/0975-7406.116828
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C9 gene polymorphism in phenytoin induced gingival enlargement: A case report

Abstract: Gingival enlargement comprises any clinical condition in which an increase in the size of the gingiva is observed. Among the drugs that induce gingival enlargement, the antiepileptic agent phenytoin has been widely related to this condition. The Cytochrome P450(CYP) superfamily is the most commonly involved enzymes in metabolism of drugs. Common coding region CYP variants that affects drug elimination and response has been studied in great detail. Pharmacogenetic influences on drug metabolism have been widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Reported cases of gingival enlargements were induced by different drugs; CCBs (50/119 – of which amlodipine-25;[8910111213141516171819202122232425262728] nifedipine-13;[26293031323334353637383940] verapamil-4;[41] felodipine-2;[4243] nisoldipine-1;[44] manidipine-1;[45] and unspecified CCBs-4[46]); phenytoin (11/119);[4748495051525354555657] cyclosporine (31/119);[3546585960616263646566676869707172737475] phenobarbital (4/119);[767778] sodium valproate (3/119 - including one report of congenital drug-induced gingival hyperplasia);[798081] d-penicillamine (2/119);[82] combination oral contraceptive pill-lynestrenol and ethinyl estradiol (1/119);[83] vigabatrin (1/119). [84] Cases of gingival enlargement after combination drug therapy have also been reported; a combination of cyclosporine and CCBs (11/119);[354685...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported cases of gingival enlargements were induced by different drugs; CCBs (50/119 – of which amlodipine-25;[8910111213141516171819202122232425262728] nifedipine-13;[26293031323334353637383940] verapamil-4;[41] felodipine-2;[4243] nisoldipine-1;[44] manidipine-1;[45] and unspecified CCBs-4[46]); phenytoin (11/119);[4748495051525354555657] cyclosporine (31/119);[3546585960616263646566676869707172737475] phenobarbital (4/119);[767778] sodium valproate (3/119 - including one report of congenital drug-induced gingival hyperplasia);[798081] d-penicillamine (2/119);[82] combination oral contraceptive pill-lynestrenol and ethinyl estradiol (1/119);[83] vigabatrin (1/119). [84] Cases of gingival enlargement after combination drug therapy have also been reported; a combination of cyclosporine and CCBs (11/119);[354685...…”
Section: Resultsmentioning
confidence: 99%
“…Babu et al . in 2013[47] evaluated drug metabolizing enzyme cytochrome P450 2C9 gene polymorphism in an epileptic patient under phenytoin therapy who presented with generalized gingival enlargement. The pharmacogenomic study of the patient revealed that the patient was a homozygous mutant of CYP2C9 which prompted them to substitute the drug.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that about 19% of patients taking phenytoin develop hypersensitivity reactions [ 8 ]. Not all patients taking phenytoin develop phenytoin-induced severe cutaneous adverse reactions such as DRESS, Steven-Johnson syndrome and toxic epidermal necrolysis [ 12 ]. Evidence suggests that genetic factors also might have a significant role in the pathogenesis of phenytoin-induced severe cutaneous adverse reactions [ 8 , 12 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation in the CYP2C9 gene can affect the metabolism, leading to altered phenotypes. It was discovered that CYP2C9 gene polymorphisms known to cause a 93% to 95% reduction in phenytoin clearance are important genetic factors for phenytoin-related severe cutaneous adverse reactions [ 8 , 12 - 16 ]. To investigate the genetic factors associated with phenytoin-related DRESS syndrome, we carried out a genome-wide association study, followed by direct sequencing of the associated gene and replication analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that genetic factors also might have a significant role in the pathogenesis of gingival enlargement and the patient's susceptibility to this unwanted effect. [ 10 11 ] A genetic predisposition could influence a variety of factors in the drug plaque-induced inflammation. These include gingival fibroblast functional heterogeneity, collagenolytic activity, drug metabolism, and collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%